SUPPRESSION OF GROUND ROLL AND GUIDED WAVES ON A SEISMIC RECORD WITH VIBROSEIS AS A SOURCE - NABILA IZZATI (NIM: 12313078), FARAH
Seismic records are often contaminated with noise as a result of surface seismic source usage. Vibroseis is one of many seismic surface sources which generates ground roll and guided waves that dominates the seismic record. If both type of noises aren't supressed, it would result in a nonoptimal stacked section. Guided waves are periodic events that can be predicted; thus applying predictive deconvolution should be able to suppress it. The application of predictive deconvolution requires two parameters which are operator length and prediction lag. Based on trial and error, the values of 120 ms and 8 ms are obtained for both parameters respectively. These values yield a better seismic record where guided waves are suppressed. There are a lot of methods that have been developed to suppress ground roll, amongst them are F-K Filter, Radial-Trace Filter, and Surface Wave Noise Attenuation. In this final project, the use of all three methods mentioned are attempted to suppress ground roll based on its velocity and frequency. All three methods attempted managed to suppress ground roll. Radial- Trace Filter appear to suppress ground roll better than the other two methods which produce seismic records with some residual ground roll visible. Therefore, Radial-Trace Filter is the most optimum method in suppressing ground roll in a seismic record with vibroseis as a source.